2015
DOI: 10.1155/2015/454256
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Potential New Biomarkers for Prostate Cancer Diagnosis and Prognosis Using 2D-DIGE and MS

Abstract: This study was designed to identify and validate potential new biomarkers for prostate cancer and to distinguish patients with and without biochemical relapse. Prostate tissue samples analyzed by 2D-DIGE (two-dimensional difference in gel electrophoresis) and mass spectrometry (MS) revealed downregulation of secernin-1 (P < 0.044) in prostate cancer, while vinculin showed significant upregulation (P < 0.001). Secernin-1 overexpression in prostate tissue was validated using Western blot and immunohistochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 85 publications
3
36
0
1
Order By: Relevance
“…Differences in the methylation and/or expression of smoking‐associated DMR genes LGALS3 and CLDN5 have also been associated with PCa. In particular, LGALS3 (galectin 3) has known roles in cell adhesion, tumor progression, bone metastasis, and apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the methylation and/or expression of smoking‐associated DMR genes LGALS3 and CLDN5 have also been associated with PCa. In particular, LGALS3 (galectin 3) has known roles in cell adhesion, tumor progression, bone metastasis, and apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…Only a few urinary markers were reported to be associated with prognosis (Table ). Prostatic acid phosphatase and galectin‐3 were significantly decreased in urine without manipulations from patients with biochemical relapse after prostatectomy ( n = 16) compared with patients without relapse ( n = 52) . PCA3 test at the first follow‐up biopsy was a significant predictor of upgrading to Gleason score ≥7 among 90 men with 5α‐reductase inhibitor during active surveillance.…”
Section: Prognostic Markersmentioning
confidence: 99%
“…The authors performed immunohistochemical analysis of 443 specimens from across all stages of prostate cancer progression and demonstrated that VCL expression was highest in CRPC, but negative or very low in benign prostatic hyperplasia, suggesting that VCL overexpression might contribute to prostate cancer progression by enhancing tumor cell proliferation. Geisler et al (21) recently reported that VCL expression was significantly upregulated in prostate cancer based on the analysis of prostate tissue samples by 2D-DIGE (two-dimensional difference in gel electrophoresis) and mass spectrometry (MS). Intriguingly, the authors showed that urinary VCL levels in prostate cancer patients were significantly higher than in urine from non-tumor patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies demonstrated that ITGB4 and VCL play critical roles in various types of cancer including prostate cancer (19)(20)(21)(22)(23)(24)(25)(26), their roles in taxane-resistant prostate cancer have not been clarified. we therefore knocked down ITGB4 and VCL expression by siRNA transfection and examined the effect of silencing on proliferation and taxane-resistance.…”
Section: Itgb4 and Vcl Knockdown Does Not Affect Proliferation And Tamentioning
confidence: 99%